Pengembangan Bahan Ajar Menulis Cerpen Berbasis Teks dengan Metode Cerpen-Gram - Sukistiono Sukistiono; Edi Suyanto; Siti Samhati (Universitas Lampung, 2018)
The purpose of this research is to develop text-based short story writing materials with short story method for SMP class IX and describe the feasibility in learning. This research uses research and development method. Borg Gall's research procedures are adapted into three stages: preliminary research, development of teaching materials, and teaching materials products. Data collection techniques used questionnaires, observations, and interviews. A limited field trial was conducted at SMPN 1 Banjit. Major field trials in SMPN 1 Baradatu, SMPN 2 Banjit, and SMPN 3 Baradatu. Quantitative data is converted to qualitative data to obtain a description of the data. The development of teaching materials begins with building context, modeling, preconstruction, and construction. The short-gram method is implemented at the pre-construction and construction stage. Teaching materials are able to create effective learning. The average value of respondents 83, learning completeness 89% when converted got A category